IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK KEPRIBADIAN SISWA PADA MATA PELAJARAN AKIDAH AKHLAK - Wiljaksana, Sultan Hegga; Yaenuri, Ali Ahmad (Dirasa Islamiyya: Journal of Islamic Studies, 2025)
Character education has an important role in shaping students' personalities to be noble, disciplined, and responsible. The subject of Akidah Akhlak is one of the main instruments in instilling character values to students, in order to form a religious, honest, and independent person. This research usesd a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The purpose of this study is to analyse the implementation of character education in Akidah Akhlak learning, identify the strategies applied in shaping students' personalities, and explore the supporting and inhibiting factors in the implementation of character education. The results showed that the implementation of character education can be done through various strategies, such as the integration of character values in learning materials, teacher exemplary, and extracurricular activities such as congregational prayers, istigasah, and the Qur'an tahfidz programme.